Investigation of the Anisotropic Patterns in the Altimeter Backscatter Measurements Over Ocean Wave Surfaces - Xu, Xi-Yu; Xu, Ke; Jiang, Maofei; Geng, Bingxu; Shi, Lingwei (Frontiers in Earth Science, 2021)
This articles attempts to analyze the influence of the anisotropic effects of the ocean wave surface on SAR altimetry measurements, which has not been intensively addressed in publications. Data of Sentinel-3A and Jason-3 altimeters allocated by WW3 numeric wave model were analyzed and the patterns of backscatter coefficient with respect to the wave direction were acquired under ~ 2m sea state. The ocean waves were classified into six categories, among which the moderate swell and short win-wave cases were analyzed intensively. Swell-dominated ocean surface shows more regularity than wind-wave-dominated ocean surface. Clear and significant sinusoid trends are found in the Sigma-0 and SSB patterns of both operational modes (SAR mode and PLRM mode) of Sentinel-3A altimeter for the moderate swell case, indicating the sensitivity to the anisotropic features of the altimeter measurements. By comparing the anisotropic patterns of two orthogonally polarized SAR altimeters (Sentinel-3A and Cryosat-2), we could draw the conclusion that the patterns are not sensitive to the polarization mode. The anisotropic effects may introduce errors in the wind speed and sea state bias (in turn, sea level) products of the SAR altimeters. For the Sigma-0 or wind speed measurements, the anisotropic errors seem to be similar for the two modes, while for the SSB estimation, the anisotropic errors for SAR mode would be almost 40% larger than that of the PLRM mode.